Resistance, Repression, and Gender Politics in Occupied Palestine and Jordan - Hasso, Frances S.; Hasso, Frances S. (Syracuse (New York) Syracuse University Press, 2005)
This book focuses on the central party apparatus of the Democratic Front for the Liberation of Palestine (DFLP), the Democratic Front (DF) branches established in the Occupied Palestinian Territories and Jordan in the 1970s, and the most influential and innovative of the DF women$1 (Bs organizations: the Palestinian Federation of Women$1 (Bs Action Committees in the occupied territories. Until now, no study of a Palestinian political organization has so thoroughly engaged with internal gender histories. In addition, no other work attempts to systematically compare branches in different regional locations to explain those differences. Students of gender and Middle East studies, especially those with a specialty in Palestinian studies, will find this work to be of critical importance. This book will also be of great interest to those working on political protest movements and factional ties.s
English
Keywords: Asian history; Gender Politics; Palestine; Jordan; Women